The Use of Address Forms Related to Social Factors and Proxemic in 12 Angry Men Movie - Veno Elriyan; Yessy Marzona (Fakultas Sastra Universitas Ekasakti, 2019)
This research discusses the use of address forms created in a conversation in a film entitled 12 Angry Men [1957).This study was conducted to look at the forms of address forms used by participants and related to social factors that influence the choice of address form, as well as the relationship between the choice of address forms and the types of proxemics that occurs between participants. In writing this thesis, the observation method is taken as a method of collecting the data. For method of analyzing the data, the writer uses the content analysis method by analyzing the content of primary data. Technique of collecting the data using qualitative techniques by taking notes in collecting primary data. In the technique of analyzing the data, the writer uses the content analysis technique. From the 20 data analyzed, it was found that there were three types of address forms present in this movie. The first type is the Title with a percentage of 75 percent. The second type is the Nickname with a percentage of 15 percent. The last type is a combination of some forms with a percentage of 10 percent. The social factors that influence the choice of address forms in this film are due to social status, particular occasion and occupational hierarchy. Whereas in proxemic is dominated by the use of social distance. It can be concluded that the occurrence of variations in the use of address forms can be caused by various social factors, and the use of distance (proxemics) and address forms occur at the same time.